Association of Household Food Insecurity With Dietary Intakes and Nutrition-Related Knowledge, Attitudes, and Practices Among School-Aged Children in Gaza Strip, Palestine - El Bilbeisi, Abdel Hamid; Al-Jawaldeh, Ayoub; Albelbeisi, Ali; Abuzerr, Samer; Elmadfa, Ibrahim; Nasreddine, Lara (Frontiers in Nutrition, 2022)
Background: The present study aimed to determine the association of household food insecurity with dietary intakes and nutrition-related knowledge, attitudes, and practices (KAP) among school-aged children. Methods: This cross-sectional study was conducted among a representative sample of school-aged children. A total of 380 children and their parents were selected from all Gaza strip governorates, using a random sampling method. The demographic and socioeconomic characteristics; the Radimer/Cornell food security scale; two non-consecutive days of 24-hour dietary recall; anthropometric measurements; and the Food and Agriculture Organization KAP-questionnaire (Module 3) were employed. Statistical analysis was performed using SPSS version 25. Results: About 71.6% of school-aged children were household food-insecure, while 28.4% were household food-secure. Significant associations were found between living area, educational level, household monthly income, weight for age and BMI for age z-scores, underweight, malnutrition status, intakes of protein, iron, vitamin D, and zinc among household food-secure, and household food-insecure. After adjustment for confounding variables, having nutrition-related adequate KAP were associated with lower odds of being food-insecure household (OR = 0.519, 95% CI = [0.320-0.841]), (OR = 0.510, 95% CI = [0.315-0.827]), and (OR = 0.466, 95% CI = [0.285-0.763], P-values < 0.05 for all), respectively. Conclusions: Low socioeconomic status, low anthropometric indices, poor dietary intakes may be associated with a high level of food-insecurity; while having nutrition-related adequate KAP may be protective against food-insecurity among school-aged children.